Vitamin D Levels and Risk Factors in Early Onset Preeclampsia, Late Onset Preeclampsia and Normal Pregnancy - Basyir, Vaulinne; ayunda, aldina ayunda insani; Andriani, Feni; Suhaila, Afifah (Indonesian Journal of Obstetrics and Gynecology, 2024)
Abstract Objective: To determine the frequency distribution and the relation of risk factors to vitamin D levels in women with early onset (EOSPE), late-onset severe preeclampsia (LOSPE), and normal pregnancy. Methods: This study was cross-sectional with pregnant women diagnosed with EOSPE LOSPE at RSUP DR M Djamil Padang and normal pregnancy at the Pengambiran Health Center. The serum samples of the research subjects were examined for blood levels of Vitamin D using the ELISA kit. Results: Frequency distribution of risk factors for EOSPE respondents aged 20-35 years 50%, mothers not working 85%, single pregnancy 95%, normal blood sugar 80%, and an increase in the number of leukocytes 90%. Frequency distribution of LOSPE respondents, maternal age 20-35 years 60%, mothers not working 95%, single pregnancy 95%, normal blood sugar 65%, and increasing leukocytes 75%. Based on the data analysis test EOSPE respondents with risk factors for preeclampsia history and body mass index had a significant relation with vitamin D levels with P Value 0.00 (P < 0.05). LOSPE mothers with gravid risk factors, history of preeclampsia, history of hypertension, and history of Diabetes Mellitus had a significant relation with Vitamin D levels P Value 0.00 (P < 0.05). Conclusion: The results of statistical tests for LOSPE mothers had a significant relation with Vitamin D levels compared to the risk factors for EOSPE mothers. The incidence of preeclampsia is influenced by complex etiopathogenesis, one of which is influenced by vitamin D levels. Keywords: EOSPE, LOSPE, Elisa-kit, Vitamin D, Etiopathogenesis